Studies on the Effects of Reducing the Period of Using Starter Mesh and Application of Probiotics to Broiler Chickens - Dube, S.; Mwenje, E.; Gora, K.; Dube, C. (International Journal of Poultry Science, 2009)
Two sets of 150 day old broiler chickens were fed with starter mesh for 14 and 21 days respectively and there after given grower mesh until day 35 after which both were fed on finisher until day 42. There was no significant difference in the final carcass mass of both (p>0.05). Another trial was set up to investigate the effect of application of probiotics as liquid and as powder on 2500 birds per treatment and a control with no probiotics was also set up. The results showed that probiotics applied as liquid had the best effect on PEF and FCR. The experiment to determine the best time to apply probiotics was conducted on 2000 birds per treatment. The results showed that the best performance was obtained when application of probiotics was started at 14 days The PEF was also highest on birds which started probiotics on day 14.